Significación del pensamiento de Francisco Suárez en el pensamiento argentino - Santiago, Dulce María (Sapientia, 2019)
Around 1940, on the proximity of the celebration of the Fourth Centenary of the birth of “Doctor Eximio”, the studies about the author and his influence on philosophical thought, both in Europe and in America, reappear. In Argentina, promoted by the "Victoria y Suárez" Foundation, the work of Father Guillermo Furlong Cardiff S.J.: "Birth and Development of Philosophy in the River Plate" (1947), which studies the gravitation of Suarez's legal-political thinking in the emancipation movement of 1810. For this thinker, it was the doctrine of Suarez popular sovereignty - taught by the Jesuits in these lands before their expulsion in 1767 - and not the ideas of the French Enlightenment, which influenced most decisively in the May Revolution. In 1949, at the First National Congress of Philosophy held in Mendoza, Father Enrique Pita S.J. speaks in a plenary session on Suárez in commemoration of its Fourth Centennial. Father Ismael Quiles S.J.-formed in Suarez's philosophy and disciple of Pita-devotes several works to the great scholastic (later compiled in a book), extolling his continuity with the philosophy of St. Thomas, as did his teacher. In the studies of Argentine Philosophical Thought of the last decades - in writers such as Leocata, Scannone, Galli, among others - the teaching of Suárez is re-read as a fundamental link for the understanding of our identity.